Digital Game in Young Children's Numeracy Skill: An Innovation through Learning Media Development - Syarfina, Syarfina; Masruroh, Siti; Masyitah, Nur; Sahpitri, Yulia; Pratiwi, Aulia Desi (Jurnal Pendidikan Anak, 2023)
Children’s numeracy skills significantly influence their readiness to enter primary school. However, teachingnumeracy to children in concrete periods is still a big challenge for teachers. Moreover, technologybasedlearning media must still be considered appropriate for early introduction. This research aims todevelop an interactive digital learning media to improve early childhood numeracy skills. This Researchand Development (RD) method used the 4-D model, which consists of Defining, Designing, Developing,and Disseminating. Expert validators who test the feasibility of the product consist of material, media, andlanguage experts. Respondents in this study were ten children aged 4-5 years at PAUD Nurul Aisyah, EastAceh. The results showed that this digital game is feasible as a learning media to improve early childhoodnumeracy skills. The average validator score for product feasibility is in the very good category, andchildren’s numeracy skills are in the good category. With this learning media, "Numb Game," childrenlearn the concepts of counting, grouping, and simple statistics. Through an interactive approach, thedevelopment of Numb Game media can stimulate children’s engagement in the numeracy learning processby utilizing visual elements, games, and interactions that stimulate curiosity and desire to understandmathematical concepts. Therefore, this interactive digital learning media presents an interesting, adaptive,and effective learning experience according to children’s needs in improving numeracy skills at an earlyage. Further research on the long-term effects of using digital learning media on the development of earlychildhood numeracy skills and the implications for their academic achievement is warranted.